Burden of occupational cancer in Ontario: major workplace carcinogens and prevention of exposure - Occupational Cancer Research Centre, Toronto; Cancer Care Ontario, Toronto (Toronto, 2017)
"Burden of Occupational Cancer in Ontario presents estimates of occupational exposure and the associated burden of cancer by industry, as well as exposure reduction strategies for the most common occupational carcinogens in Ontario. A major feature of the report is the evidence-based policy recommendations directed at government, Ontario’s occupational health and safety system, employers and non-governmental organizations. Burden of Occupational Cancer in Ontario was jointly produced by the Occupational Cancer Research Centre and Cancer Care Ontario’s Population Health and Prevention team, with input from experts on scientific content and policy recommendations. The occupational carcinogen exposure estimates were provided by CAREX Canada. Key findings of the report include: Solar radiation, asbestos, diesel engine exhaust and crystalline silica had the largest estimated impact on cancer burden and also the highest number of Ontario workers exposed Solar Radiation: Approximately 450,000 Ontario workers are exposed, causing an estimated 1,400 non-melanoma skin cancer cases per year Asbestos: Fewer than 55,000 workers are exposed but it is estimated to cause 630 lung cancers, 140 mesotheliomas, 15 laryngeal cancers and less than five ovarian cancers annually Diesel Engine Exhaust: About 301,000 workers are exposed every year and it accounts for 170 lung and 45 bladder cancer cases Crystalline Silica: An estimated 142,000 Ontario workers are exposed to crystalline silica, which annually causes almost 200 lung cancer cases Through policy changes and workplace-based measures there are many opportunities to reduce the burden of occupational cancer in Ontario."